Factors Influencing Farmers’ Decision to Adopt Apple Management Practices in Southwestern Highlands, Uganda - Rwaheru Aheisibwe, Ambrose; Tindimwebwa, Kenneth; Ashaba, Denis; Barekye, Alex (Journal of Economics and Sustainable Development, 2019)
Worldwide apples account for fifty (50) percent of the world’s deciduous fruit tree production. Despite the benefits that come with apple production, adoption has been slow especially among smallholder farmers in Southwestern Highlands. This present study was therefore conducted to identify apple management practices (AMPs) and also examine the factors influencing farmer decision to adopt AMPs. A multi-stage sampling procedure was employed to select 52 apple growing households in the districts of Kabale, Kisoro, Kanungu and Rukungiri that form Southwestern Highlands. Probit regression model was employed and the estimation procedure followed Maximum Likelihood Estimation (MLE) approach. Results from the descriptive statistics indicated that the most applied management practices included weeding, bending and staking, pesticide application and defoliation among others. Probit regression results showed that sex of the farmer, average number of fruits per tree, household labor force, farm size and access to credit had a positive and statistically significant effect on farmers’ decision to adopt AMPs (p<0.05) while age of the farmer, orchard location, obstruction by birds and off-farm income source had a negative and statistically significant influence on farmers’ decision to adopt AMPs (p<0.05). In view of the above, there is need to identify and address gender differences in terms of engagement in apple production targeting more women. Research needs to come up with an effective but affordable remedy against pests especially birds, strategies of attracting and maintaining youth into apple farming need to be explored and implemented since apple farming is labor intensive and is dominated by aging farmers, research and extension need to explore appropriate and cost effective avenues for farmers to access credit, accurate and quality agricultural information.
Keywords: Adoption; Apples; Probit model; Orchard; Southwestern Highlands